The cell cycle regulatory gene polymorphisms TP53 (rs1042522) and MDM2 (rs2279744) in lung cancer: a meta-analysis - O. Bulgakova; A. Kussainova; R. Bersimbaev (Вавиловский журнал генетики и селекции)
Lung cancer is one of the most common types of cancer in the world. Although the mechanism of lung cancer is still unknown, a large number of studies have found a link between gene polymorphisms and the risk of lung cancer. The tumor suppressor p53 plays a crucial role in maintaining genomic stability and tumor prevention. MDM2 is a critical regulator of the p53 protein. Despite the importance of p53 pathway in cancer, data on the contribution of SNPs of TP53 (rs1042522) and MDM2 (rs2279744) to the development of lung cancer are very contradictory. A metaanalysis that collects quantitative data from individual studies and combines their results has the advantage of improving accuracy, providing reliable estimates, and resolving those issues in which studies on individual associations are not effective enough. The aim of this study was to determine whether the TP53 (rs1042522) and MDM2 (rs2279744) polymorphisms confer susceptibility to lung cancer. A meta-analysis was conducted on the associations between the TP53 (rs1042522) and MDM2 (rs2279744) polymorphisms and lung cancer. A total of 51 comparison studies including 25,366 patients and 25,239 controls were considered in this meta-analysis. The meta-analysis showed no association between lung cancer and MDM2 (rs2279744) under any model. A noteworthy association of TP53 (rs1042522) with susceptibility to lung cancer in overall pooled subjects was observed under three different models (allele contrast, homozygote contrast (additive) and dominant). Stratification by ethnicity indicated an association between the TP53 (rs1042522) and lung cancer in Asians and Caucasians. This meta-analysis demonstrates that the TP53 (rs1042522), but not MDM2 (rs2279744) polymorphism may confer susceptibility to lung cancer.